Dysfunction of hypothalamic-hypophysial axis after traumatic brain injury in adults - Krahulik, David; Zapletalova, Jirina; Frysak, Zdenek; Vaverka, Miroslav (Journal of neurosurgery, 2010)
OBJECT: Traumatic brain injury (TBI) is a major cause of serious morbidity and mortality. The incidence is 100-500/100,000 inhabitants/year. Chronic pituitary dysfunction is increasingly recognized after TBI. To define the incidence of endocrine dysfunction and risk factors, the authors describe a prospectively assessed group of patients in whom they documented hormonal functions, early diagnosis, and treatment of neuroendocrine dysfunction after TBI. METHODS: Patients aged 18-65 years were prospectively observed from the time of injury to 1 year postinjury; the Glasgow Coma Scale score ranged from 3 to 14. Patients underwent evaluation of hormonal function at the time of injury and at 3, 6, and 12 months postinjury. Magnetic resonance imaging was also conducted at 1 year postinjury. RESULTS: During the study period, 89 patients were observed. The mean age of the patients was 36 years, there were 23 women, and the median Glasgow Coma Scale score was 7. Nineteen patients (21%) had primary hormonal dysfunction. Major deficits included growth hormone dysfunction, hypogonadism, and diabetes insipidus. Patients in whom the deficiency was major had a worse Glasgow Outcome Scale score, and MR imaging demonstrated empty sella syndrome more often than in patients without a deficit. CONCLUSIONS: To the authors' knowledge, this is the third largest study of its kind worldwide. The incidence of chronic hypopituitarism after TBI was higher than the authors expected. After TBI, patients are usually observed on the neurological and rehabilitative wards, and endocrine dysfunction can be overlooked. This dysfunction can be life threatening and other clinical symptoms can worsen the neurological deficit, extend the duration of physiotherapy, and lead to mental illness. The authors recommend routine pituitary hormone testing after moderate or severe TBI within 6 months and 1 year of injury.
Keywords: Magnetic Resonance Imaging; poranění mozku; magnetická rezonanční tomografie; Humans; lidé středního věku; Hypopituitarism; Chronic Disease; hormony; rizikové faktory; mladý dospělý; dospělí; Aged; Female; senioři; lidé; systém hypotalamus-hypofýza; Hormones; časové faktory; Endocrine System Diseases; Adult; Follow-Up Studies; ženské pohlaví; stupeň závažnosti nemoci; Male; Middle Aged; chronická nemoc; Adolescent; incidence; Incidence; nemoci endokrinního systému; Severity of Illness Index; hypopituitarismus; Young Adult; Brain Injuries; mužské pohlaví; prospektivní studie; Hypothalamo-Hypophyseal System; Time Factors; následné studie; mladiství; Risk Factors; Prospective Studies